2015
DOI: 10.1002/bio.3042
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the spectrofluorimetric determination of cefdinir through a Taguchi experimental design approach

Abstract: The aim of this work is to optimize a spectrofluorimetric method for the determination of cefdinir (CFN) using the Taguchi method. The proposed method is based on the oxidative coupling reaction of CFN and cerium(IV) sulfate. The quenching effect of CFN on the fluorescence of the produced cerous ions is measured at an emission wavelength (λ(em)) of 358 nm after excitation (λ(ex)) at 301 nm. The Taguchi orthogonal array L9 (3(4)) was designed to determine the optimum reaction conditions. The results were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…The preconcentration factor achieved was of 50 fold led to obtaining the limit of detection (LOD) of 0.21 μgmL −1 ( Table 1). Concerning LOD, our findings was better than with the results obtained by Singh et al, 6 , Wagh et al, 9 , Shinde et al, 14 , Abou-Taleb et al, 15 and Pant et al, 16 . But, it was in agreement with works of Patel et al, 7 and Hanwen et al, 10 .…”
Section: Calibration Graphs For Nor Drug and Iron(iii) Ionscontrasting
confidence: 80%
See 1 more Smart Citation
“…The preconcentration factor achieved was of 50 fold led to obtaining the limit of detection (LOD) of 0.21 μgmL −1 ( Table 1). Concerning LOD, our findings was better than with the results obtained by Singh et al, 6 , Wagh et al, 9 , Shinde et al, 14 , Abou-Taleb et al, 15 and Pant et al, 16 . But, it was in agreement with works of Patel et al, 7 and Hanwen et al, 10 .…”
Section: Calibration Graphs For Nor Drug and Iron(iii) Ionscontrasting
confidence: 80%
“…Figure 1. Chemical structure of norfloxacin Many instrumental methods have been reported in chemical literature revealed that this medicament was determined alone or in combined dosage form including; high performance liquid chromatographic methods [5][6][7][8] , electroanalytical methods [9][10][11] , electro-generated chemiluminescence 12 , atomic absorption spectrometry 13 and spectrophotometry [14][15][16][17] . Although of these methods, NOR is the subject of a monograph in most international pharmacopoeias such as the British Pharmacopoeia, BP 3 , United States Pharmacopoeia, USP 18 and Indian Pharmacopoeia 19 , which have recommended a non aqueous titration for the raw material and HPLC technique for tablets.…”
Section: Research Articlementioning
confidence: 99%
“…In the literature, various analytical methods were described for the quantification of cefdinir alone and in combination with other drugs in pharmaceutical preparations and biological fluids using spectrofluorimetry [2], spectrophotometry [3][4][5], high-performance liquid chromatography [5][6][7][8][9][10][11], liquid chromatography-mass spectrometry [12][13][14], capillary electrophoresis-mass spectrometry [14]. Electrochemical behavior of cefdinir has been well reported in the literature [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers have been extensively studied for the development of drug sensors based on their high conductivity, fast response times, and room temperature operation. The review of literature revealed that a few methods have been explored for the detection of TNZ, which includes titrimetric, 51 TLC, 52 spectrophotometric, [53][54][55] HPLC, 56 RP-HPLC 57,58 , and UV-visible spectrophotometry. [45][46][47][48] Tinidazole (TNZ), chemically 1-(2-ethyl sulfonyl ethyl)-2-methyl-5-nitroimidozole [A] is an antiparasitic drug used against protozoan infection including giardiasis, amoebiasis, and vaginal trichomoniasis.…”
Section: Introductionmentioning
confidence: 99%